432 THE EPIDEMIOLOGY OF DENGUE FEVER IN PALAU. Issue 1 (1st January 2007) - Stevens, A. M.; Carter, K.
Abstract : Background: Dengue fever has been a long-standing problem in Palau, and public health programs were implemented in 2000 to conduct surveillance for cases of the disease. Epidemiologic analysis of dengue fever cases in Palau is needed to describe disease occurrence in Palau and to help target prevention and control efforts. Methods: Case data were collected from the Palau Ministry of Health's Reportable Disease Surveillance System. Descriptive epidemiology was performed on the case data, and spatial analysis was used to assess the distribution of dengue fever cases in Palau. Results: Between 2001 and June of 2006, 676 cases of dengue fever occurred in Palau, and sporadic outbreaks without seasonality were noted. Characteristics of the case population included being male (57.8%), being under the age of 20 (mean age 23.4 years), being Palauan (88.2%), having an indoor occupation (91.7%), and having no history of travel outside Palau during the estimated exposure period (96.3%). Most cases also lived in urban areas of Palau (92.0%), and the disease rate was significantly higher in urban areas compared with rural areas (3, 941.8 vss 1, 175.7 cases per 100, 000, respectively; p = .0007). Conclusion: This study supports the idea that dengue fever is still endemic in Palau. Control and prevention measures should be continued and targeted toward urban areas and populations at increased risk of this disease.